Double-layer antibacterial composite film containing nano cuprous oxide, preparation method and application of double-layer antibacterial composite film

Through the bilayer structure of nanocubous cuprous oxide/carboxymethyl chitosan and polyvinyl alcohol, an antibacterial double-layer composite film is prepared in one step by freeze-drying method, solving the complexity and biosafety problems of the existing technology and achieving high efficiency. Stable antibacterial effect, suitable for biomedical field.

CN119280483APending Publication Date: 2025-01-10JIAXING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411164035.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing antibacterial bilayer composite membrane preparation process is complex, and nanoantibacterial agents may cause cytotoxicity when released in the body, affecting biosafety.

Method used

The two-layer structure of nanocubous cuprous oxide/carboxymethyl chitosan layer and polyvinyl alcohol layer was prepared in one step by freeze-drying. The nanocubous cuprous oxide was evenly distributed in carboxymethyl chitosan to form a loose structure to avoid Direct contact with the skin and use glutaraldehyde cross-linking to improve stability.

Benefits of technology

It achieves a simple, safe and effective antibacterial effect. The microstructure is similar to an extracellular matrix, which is conducive to tissue repair, is simple to operate, is low in cost, and is highly stable. It is suitable for the fields of antibacterial and biomedical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280483A_ABST
    Figure CN119280483A_ABST
Patent Text Reader

Abstract

The invention relates to a nano cuprous oxide-containing double-layer antibacterial composite film, a preparation method and application thereof, the composite film is of a double-layer structure, one layer is a nano cuprous oxide / carboxymethyl chitosan layer, and the other layer is a polyvinyl alcohol layer; the antibacterial double-layer composite film containing the nano cuprous oxide is of a double-layer structure, one layer is a nano cuprous oxide / carboxymethyl chitosan layer, the other layer is a polyvinyl alcohol layer, and the nano cuprous oxide can be uniformly distributed in carboxymethyl chitosan, so that the antibacterial double-layer composite film containing the nano cuprous oxide has the advantages that the antibacterial double-layer composite film containing the nano cuprous oxide can be used for preparing the antibacterial double-layer composite film containing the nano cuprous oxide; the microstructures of the two-layer composite membrane are different, the nano cuprous oxide / carboxymethyl chitosan layer is loose, and the pore diameter and porosity are larger than those of polyvinyl alcohol, so that the two different microstructures are more similar to the structure of an extracellular matrix, and tissue repair is more facilitated in the application process; the double-layer film can be widely applied to the fields of antibiosis and biomedicine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of biomedical materials, and specifically relates to a double-layer antibacterial composite film containing nano-cuprous oxide, a preparation method and an application thereof. Background Art

[0002] In the field of biomedicine, in tissue engineering applications, bacterial infectious diseases caused by tissue engineering scaffold transplantation have always been a difficult problem to solve. In the process of wound healing, bacterial infection often leads to delayed healing and increased morbidity. Therefore, the antibacterial properties of tissue engineering scaffolds and wound dressings are particularly important. At present, various antibacterial agents are added to tissue engineering scaffolds or wound dressings to give them antibacterial properties, especially nanoparticles with broad-spectrum antibacterial properties and no drug resistance, such as nanosilver, nanozinc oxide, nanotitanium oxide, nanomagnesium oxide, nanocuprous oxide, etc. However, the potential cytotoxicity caused by the uncontrolled release of these antibacterial agents and direct contact with the body is not only potentially harmful to local tissues, but can also enter the body through the circulatory system, posing a threat to the health of the body.

[0003] Therefore, in order to avoid the potential harm caused by direct contact between the antibacterial agent and human skin, Chinese patent CN103816561A discloses a silk-based double-layer antibacterial film and a preparation method thereof, wherein the silk-based film containing nano-silver is first prepared, and then the silk-based film containing pearl powder is connected together on the silk-based film by self-assembly of silk to form an antibacterial double-layer film, wherein the silk-based film containing nano-silver is on the outer layer, thereby overcoming the potential biological safety of nano-silver; in addition, Chinese patent CN110396209A discloses a method having antibacterial A method for preparing a functional double-layer silk film, wherein the double-layer silk film is prepared by a casting method, wherein the outer layer is a silk-based film containing nano-magnesium oxide, and the inner layer is a silk-based film containing menthol-aloe vera, thereby avoiding potential harm caused by direct contact between nano-magnesium oxide and human skin; in addition, Chinese patent CN108653816A discloses a method for preparing a double-layer artificial antibacterial repair film by electrospinning, wherein an outer layer of a polycaprolactone film containing nano-zinc oxide is first prepared by an electrospinning method, and then a layer of a polylactic acid film containing hydroxyapatite is electrospun.

[0004] However, the above-mentioned prior arts require multiple steps to prepare the antibacterial double-layer composite membrane, and the process is relatively complicated. Summary of the invention

[0005] In order to solve the above problems, the present application provides a simple process, which can prepare an antibacterial double-layer composite film containing nano-cuprous oxide by mixing two materials and then simply freeze-drying them.

[0006] In order to solve the above technical problems, the technical solution adopted in the present application is: an antibacterial double-layer composite film containing nano-cuprous oxide, the composite film has a double-layer structure, one layer is a nano-cuprous oxide / carboxymethyl chitosan layer, and the other layer is a polyvinyl alcohol layer; the nano-cuprous oxide is distributed in the carboxymethyl chitosan.

[0007] Furthermore, the structure of the nano cuprous oxide / carboxymethyl chitosan layer is relatively loose, and the pore size and porosity are greater than those of the polyvinyl alcohol layer.

[0008] Furthermore, the nano cuprous oxide / carboxymethyl chitosan layer and the polyvinyl alcohol layer are obtained by freeze drying.

[0009] The present application also provides a method for preparing the above-mentioned nano-cuprous oxide-containing antibacterial double-layer composite film, and the specific preparation steps thereof include:

[0010] (1) dissolving a nano-cuprous oxide / carboxymethyl chitosan porous sponge in deionized water to prepare a nano-cuprous oxide / carboxymethyl chitosan solution;

[0011] (2) dissolving polyvinyl alcohol in deionized water above 95° C. to prepare a polyvinyl alcohol solution;

[0012] (3) The nano-cuprous oxide / carboxymethyl chitosan solution prepared in step (1) and the polyvinyl alcohol solution prepared in step (2) are blended to prepare a blended solution, and then the blended solution is pre-frozen at -30°C to -60°C for 4-8 hours, and then freeze-dried to dryness to prepare a nano-cuprous oxide-containing double-layer antibacterial composite film.

[0013] Furthermore, the concentration of the nano cuprous oxide / carboxymethyl chitosan solution in step (1) is 1-4 wt %, that is, the concentration of the nano cuprous oxide / carboxymethyl chitosan porous sponge in the solution.

[0014] Furthermore, the nano cuprous oxide / carboxymethyl chitosan porous sponge described in step (1) is specifically prepared by the following method: adding carboxymethyl chitosan to deionized water and stirring at room temperature to prepare a 4wt% carboxymethyl chitosan solution; taking 20mL of the carboxymethyl chitosan solution, adding 20mL of 0.08mol / L copper sulfate solution and stirring for 2 hours; adding 0.2mol / L sodium hydroxide (NaOH) solution to adjust the pH to 12; then adding 48mL of 0.16mol / L vitamin C solution and reacting for 24 hours; placing the obtained solution into a dialysis bag, dialyzing with deionized water for 72 hours; pre-freezing the dialyzed solution at -60°C for 6 hours; and then freeze-drying to dryness to obtain the nano cuprous oxide / carboxymethyl chitosan porous sponge.

[0015] Furthermore, the concentration of the polyvinyl alcohol solution in step (2) is 1-8 wt %, that is, the concentration of polyvinyl alcohol in the solution.

[0016] Furthermore, the volume ratio of the nano cuprous oxide / carboxymethyl chitosan solution to the polyvinyl alcohol solution in step (3) is 1:9-5:5.

[0017] Furthermore, the freeze-drying time in step (3) is 24-48 hours.

[0018] Furthermore, the step also includes cross-linking the prepared nano-cuprous oxide-containing double-layer antibacterial composite film with 50wt% glutaraldehyde vapor to make it insoluble in water.

[0019] The present application also provides an application of the above-mentioned nano-cuprous oxide-containing antibacterial double-layer composite film in the antibacterial and biomedical fields.

[0020] Advantages and beneficial effects of this application:

[0021] (1) The antibacterial double-layer composite film containing nano-cuprous oxide of the present application is a double-layer structure, wherein one layer is a nano-cuprous oxide / carboxymethyl chitosan layer, and the other layer is a polyvinyl alcohol layer, and the nano-cuprous oxide can be evenly distributed in the carboxymethyl chitosan, and the two-layer composite film of the present application has different microstructures, the nano-cuprous oxide / carboxymethyl chitosan layer is relatively loose, and the pore size and porosity are larger than those of polyvinyl alcohol, that is, the structure of the nano-cuprous oxide / carboxymethyl chitosan layer is looser than that of the other layer, so its pore size and porosity are also larger, so that the two layers of different microstructures are more similar to the structure of the extracellular matrix, and therefore, it will be more conducive to tissue repair during the application process; this double-layer membrane can be widely used in the antibacterial and biomedical fields.

[0022] (2) After mixing the two materials, the present application adopts a simple freeze-drying method to prepare a double-layer antibacterial composite film containing nano-cuprous oxide in one step. The operation is very simple. The entire reaction system uses water as a solvent, which is energy-saving and environmentally friendly, low-cost and easy to control.

[0023] (3) The carboxymethyl chitosan and cuprous oxide of the present application both have antibacterial properties, so the prepared double-layer antibacterial composite film has a synergistic antibacterial effect, and the antibacterial effect is more ideal.

[0024] (4) The present application firstly adopts an in-situ reduction method to prepare a nano copper oxide / carboxymethyl chitosan composite, the reaction mechanism of which is that carboxymethyl chitosan forms a complex with copper sulfate, and vitamin C is used to reduce copper ions to cuprous oxide under alkaline conditions. The reaction formula is as follows:

[0025]

[0026] The in-situ reduction method can be used to evenly combine the nano cuprous oxide particles with the carboxymethyl chitosan. The carboxymethyl chitosan molecular chain can hinder the agglomeration of the nano cuprous oxide particles and increase the stability of the nano cuprous oxide. Then the nano cuprous oxide / carboxymethyl chitosan complex solution is blended with a polyvinyl alcohol solution. Since the cuprous oxide is chelated on the carboxymethyl chitosan molecular chain, the molecular chain shrinks and the density increases, so that phase separation occurs during the low-temperature freezing process. After freeze drying, an antibacterial double-layer film containing the nano cuprous oxide can be formed, and the nano cuprous oxide can be evenly dispersed in the carboxymethyl chitosan.

[0027] (5) The double-layer antibacterial composite film containing nano-cuprous oxide prepared in the present application can be cross-linked by using 50wt% glutaraldehyde vapor. The cross-linked double-layer antibacterial composite film containing nano-cuprous oxide is insoluble in water, so that it has higher stability in subsequent use. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a macroscopic photo of the antibacterial double-layer composite film containing nano-cuprous oxide:

[0029] (a) is the surface of the polyvinyl alcohol layer;

[0030] (b) is the surface of nano-oxide / carboxymethyl chitosan layer.

[0031] Figure 2 This is a scanning electron microscope image of the cross section of the antibacterial double-layer composite membrane containing nano-cuprous oxide:

[0032] (a) is the cross section of the antibacterial double-layer composite film containing nano-cuprous oxide;

[0033] (b, c) are cross sections of nano-oxide / carboxymethyl chitosan layers (1000 times, 10000 times, the red arrows in the figures are nano-cuprous oxide particles);

[0034] (d, e) are cross sections of the polyvinyl alcohol layer (1000 times, 10000 times).

[0035] Figure 3 The mapping diagram and element content of copper element in the cross section of the EDS of the antibacterial double-layer composite film containing nano-cuprous oxide:

[0036] (a) EDS mapping of copper element and element content in the cross section of nano-oxide / carboxymethyl chitosan layer;

[0037] (b) EDS mapping of copper elements and element content in the cross section of the polyvinyl alcohol layer. DETAILED DESCRIPTION

[0038] The present application is further described in detail below through examples, but the present application is not limited to the following examples.

[0039] Example 1

[0040] (1) Carboxymethyl chitosan was added to deionized water and stirred at room temperature to prepare a 4 wt % carboxymethyl chitosan solution. 20 mL of the carboxymethyl chitosan solution was added to 20 mL of 0.08 mol / L copper sulfate solution and stirred for 2 hours. 0.2 mol / L sodium hydroxide solution was added to adjust the pH to 12. Then 48 mL of 0.16 mol / L vitamin C solution was added to react for 24 hours. The obtained solution was placed in a dialysis bag and dialyzed with deionized water for 72 hours. The dialyzed solution was pre-frozen at -60°C for 6 hours and then freeze-dried to dryness to obtain a nano cuprous oxide / carboxymethyl chitosan composite (nano cuprous oxide / carboxymethyl chitosan porous sponge).

[0041] (2) weighing 0.2 g of nano-cuprous oxide / carboxymethyl chitosan complex, adding it to 10 mL of water and stirring until completely dissolved to obtain a nano-cuprous oxide / carboxymethyl chitosan solution with a concentration of 2 wt %;

[0042] (3) Weighing 0.2 g of polyvinyl alcohol, adding it to 10 mL of water, heating and stirring until it is completely dissolved to obtain a polyvinyl alcohol solution with a concentration of 2 wt%;

[0043] (4) The nano-cuprous oxide / carboxymethyl chitosan solution prepared in step (2) and the polyvinyl alcohol solution prepared in step (3) were blended at a volume ratio of 2:8 for 1 hour, then poured into a culture dish, pre-frozen at -60°C for 6 hours, and then freeze-dried to dryness to obtain an antibacterial double-layer composite film containing nano-cuprous oxide, which was cross-linked with 50wt% glutaraldehyde vapor to make it insoluble in water (no heating is required, 50wt% glutaraldehyde vapor at room temperature is sufficient).

[0044] Specific products are as follows Figure 1 As shown, Figure 1 The macroscopic photographs of the antibacterial double-layer composite film containing nano-cuprous oxide, where (a) is the surface of the polyvinyl alcohol layer, and (b) is the surface of the nano-oxide / carboxymethyl chitosan layer; the surface of the polyvinyl alcohol layer is white, and the nano-oxide / carboxymethyl chitosan layer is yellow-green.

[0045] Figure 2 The scanning electron microscope images of the cross section of the nano-cuprous oxide antibacterial double-layer composite film are shown in Figure 2. (a) The cross section of the nano-cuprous oxide antibacterial double-layer composite film; (b, c) The cross section of the polyvinyl alcohol layer (1000 times, 10000 times, the red arrows in the figure are nano-cuprous oxide particles); (d, e) The cross section of the nano-cuprous oxide / carboxymethyl chitosan layer (1000 times, 10000 times); Figure 2It can be seen that the nano-cuprous oxide / carboxymethyl chitosan layer has a larger pore size and a higher porosity than the polyvinyl alcohol layer, and a large number of nano-cuprous oxide particles are distributed on the carboxymethyl chitosan (the red arrows in the figure indicate nano-cuprous oxide particles).

[0046] Figure 3 The mapping diagram and element content of copper element in the cross section of the EDS of the nano-cuprous oxide antibacterial double-layer composite film; (a) the mapping diagram and element content of copper element in the cross section of the EDS of the nano-cuprous oxide / carboxymethyl chitosan layer; (b) the mapping diagram and element content of copper element in the cross section of the EDS of the polyvinyl alcohol layer, from Figure 3 It can be seen that the copper element in the nano-cuprous oxide / carboxymethyl chitosan layer is evenly distributed on the carboxymethyl chitosan, and the copper element content is 3.3wt%, while the copper element content in the polyvinyl alcohol layer is 0wt%.

[0047] The double-sided composite film of the present application has a polyvinyl alcohol layer that fits the skin, and a nano cuprous oxide / carboxymethyl chitosan layer that is away from the skin and used as an antibacterial agent layer.

[0048] The antibacterial double-layer composite film containing nano-cuprous oxide prepared in the above embodiment is characterized, and the results show that the antibacterial double-layer composite film containing nano-cuprous oxide prepared by the one-step freeze-drying method in the present application is a double-layer structure, one layer is a nano-cuprous oxide / carboxymethyl chitosan layer, and one layer is a polyvinyl alcohol layer, and the nano-cuprous oxide can be evenly distributed in the carboxymethyl chitosan, and the microstructures of the two layers are different, the nano-cuprous oxide / carboxymethyl chitosan layer is relatively loose, and the pore size and porosity are larger than those of polyvinyl alcohol. The different microstructures of the two layers are more similar to the structure of the extracellular matrix, so it will be more conducive to tissue repair during the application process. This double-layer membrane can be widely used in the antibacterial and biomedical fields.

[0049] Example 2

[0050] The preparation of nano cuprous oxide / carboxymethyl chitosan composite is the same as that of Example 1;

[0051] Then, 0.2 g of nano cuprous oxide / carboxymethyl chitosan complex was weighed and added into 10 mL of water and stirred until completely dissolved to obtain a 2 wt % nano cuprous oxide / carboxymethyl chitosan solution;

[0052] Weigh 0.2 g of polyvinyl alcohol and add it into 10 mL of water, heat and stir until completely dissolved to obtain a 2 wt% polyvinyl alcohol solution;

[0053] Then the nano cuprous oxide / carboxymethyl chitosan solution and the polyvinyl alcohol solution were mixed in a volume ratio of 3:7 for 1 hour, poured into a culture dish, pre-frozen at -55°C for 8 hours, and then freeze-dried to dryness to obtain an antibacterial double-layer composite film containing nano cuprous oxide, which was then cross-linked with 50wt% glutaraldehyde vapor to make it insoluble in water.

[0054] Example 3

[0055] The preparation of nano cuprous oxide / carboxymethyl chitosan composite is the same as that of Example 1;

[0056] Weigh 0.2 g of nano cuprous oxide / carboxymethyl chitosan complex, add it into 10 mL of water and stir until completely dissolved to obtain a 2 wt % nano cuprous oxide / carboxymethyl chitosan solution;

[0057] Weigh 0.2 g of polyvinyl alcohol and add it into 10 mL of water, heat and stir until completely dissolved to obtain a 2 wt% polyvinyl alcohol solution;

[0058] The prepared nano cuprous oxide / carboxymethyl chitosan solution and polyvinyl alcohol solution were blended at a volume ratio of 4:6 for 1 hour, poured into a culture dish, pre-frozen at -60°C for 6 hours, and then freeze-dried to dryness to obtain a nano cuprous oxide-containing antibacterial double-layer composite film, which was cross-linked with 50wt% glutaraldehyde vapor to make it insoluble in water.

Claims

1. An antibacterial double-layer composite film containing nano cuprous oxide, characterized in that: The composite film is a double-layer structure, wherein one layer is a nano cuprous oxide / carboxymethyl chitosan layer, and the other layer is a polyvinyl alcohol layer; the nano cuprous oxide is distributed in the carboxymethyl chitosan.

2. The antibacterial double-layer composite film containing nano-cuprous oxide according to claim 1, characterized in that: The structure of the nano cuprous oxide / carboxymethyl chitosan layer is relatively loose, and the pore size and porosity are greater than those of the polyvinyl alcohol layer.

3. The antibacterial double-layer composite film containing nano-cuprous oxide according to claim 1, characterized in that: The nano cuprous oxide / carboxymethyl chitosan layer and the polyvinyl alcohol layer are obtained by freeze drying.

4. A method for preparing a nano-cuprous oxide-containing antibacterial double-layer composite film, characterized in that: The specific preparation steps include: (1) dissolving a nano-cuprous oxide / carboxymethyl chitosan porous sponge in deionized water to prepare a nano-cuprous oxide / carboxymethyl chitosan solution; (2) dissolving polyvinyl alcohol in deionized water above 95° C. to prepare a polyvinyl alcohol solution; (3) The nano-cuprous oxide / carboxymethyl chitosan solution prepared in step (1) and the polyvinyl alcohol solution prepared in step (2) are blended to prepare a blended solution, and then the blended solution is pre-frozen at -30°C to -60°C for 4-8 hours, and then freeze-dried to dryness to prepare a nano-cuprous oxide-containing double-layer antibacterial composite film.

5. The method for preparing the antibacterial double-layer composite film containing nano-cuprous oxide according to claim 4, characterized in that: The concentration of the nano cuprous oxide / carboxymethyl chitosan solution in step (1) is 1-4 wt %.

6. The method for preparing the nano-cuprous oxide-containing antibacterial double-layer composite film according to claim 4, characterized in that: The nano cuprous oxide / carboxymethyl chitosan porous sponge described in step (1) is specifically prepared by the following method: adding carboxymethyl chitosan to deionized water and stirring at room temperature to prepare a 4wt% carboxymethyl chitosan solution; taking 20mL of the carboxymethyl chitosan solution, adding 20mL of 0.08mol / L copper sulfate solution and stirring for 2 hours; adding 0.2mol / L sodium hydroxide solution to adjust the pH to 12; then adding 48mL of 0.16mol / L vitamin C solution and reacting for 24 hours; putting the obtained solution into a dialysis bag, dialyzing with deionized water for 72 hours; pre-freezing the dialyzed solution at -60°C for 6 hours; and then freeze-drying to dryness to obtain the nano cuprous oxide / carboxymethyl chitosan porous sponge.

7. The method for preparing the antibacterial double-layer composite film containing nano-cuprous oxide according to claim 4, characterized in that: The concentration of the polyvinyl alcohol solution in step (2) is 1-8wt%.

8. The method for preparing the antibacterial double-layer composite film containing nano-cuprous oxide according to claim 4, characterized in that: The volume ratio of the nano cuprous oxide / carboxymethyl chitosan solution to the polyvinyl alcohol solution in step (3) is 1:9-5:5; and the freeze-drying time in step (3) is 24-48 hours.

9. The method for preparing the nano-cuprous oxide-containing antibacterial double-layer composite film according to claim 4, characterized in that: The step also includes cross-linking the prepared nano-cuprous oxide-containing double-layer antibacterial composite film using 50wt% glutaraldehyde vapor.

10. Application of an antibacterial double-layer composite film containing nano cuprous oxide in the antibacterial and biomedical fields.

Citation Information

Patent Citations

  • Fibroin based double-layer antibiotic film and making method thereof

    CN103816561A

  • Method for preparing double-layer artificial antibacterial repair membrane using electrostatic spinning

    CN108653816A

  • Preparation method of double-layer silk fibroin membrane with antibacterial function

    CN110396209A